Case Report: A long-term response of immunotherapy combined with anti-angiogenesis therapy in a patient with dMMR metastatic colorectal cancer after ICI failure - Huang, Qianwen; Zheng, Xiaoling; Xu, Wenshen (Frontiers in Oncology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) have demonstrated significant efficacy in patients with metastatic colorectal cancer (mCRC) characterized by high microsatellite instability (MSI-H) or deficient mismatch repair (dMMR). However, most patients experience intrinsic or acquired resistance. The need for treatment for patients with MSI-H/dMMR mCRC remains unmet. Here, we report the case of a patient with dMMR mCRC who achieved a durable therapeutic benefit from the combination of ICI and angiogenesis inhibitor after ICI failure.Case presentationA 40-year-old Chinese woman diagnosed with cT4N2M1b mCRC characterized by dMMR attributed to MLH-1 and PMS-2 deficiency, along with KRAS mutation. Primarily, the patient was treated with a combination of Chinese medicine and XELOX and underwent disease progression. Due to dMMR status, this patient then received single-agent camrelizumab. Unfortunately, disease progression was observed after two cycles of treatment. Subsequently, she received camrelizumab combined with bevacizumab. After treatment, the patient achieved a complete response, and the disease was sustainably controlled with a progression-free survival (PFS) of 3 years and counting.ConclusionsThis report demonstrates that the combination of ICI and anti-angiogenesis therapy can induce a powerful and durable antitumor response in patients with ICI-resistant MSI-H/dMMR mCRC, which is worthy of further research.